A detailed investigation of a variable nozzle turbine with novel forepart rotation guide vane. (March 2019) - Yang, Dengfeng; Yang, Ce; Lao, Dazhong; Zeng, Tao
One of the disadvantages of a variable nozzle turbine in practical application is the stage performance degradation due to nozzle endwall leakage flow at small nozzle openings. Aiming at restricting the nozzle leakage flow rate to improve turbine stage performance, a novel forepart rotation guide vane has been proposed and numerically studied in present work. First, the numerical results of baseline turbine were validated by experimental data to ensure the accuracy of numerical methods. Then steady and unsteady simulations were performed on both baseline and forepart rotation guide vane turbines to demonstrate the effectiveness of the novel vane and to study the characteristics of nozzle leakage flow, respectively. Results indicate that there is up to 13.5% peak efficiency improvement that has been achieved at 10% nozzle opening with the forepart rotation guide vane design; besides, rotor–stator interaction for forepart rotation guide vane is also mitigated due to the reduced nozzle leakage flow rate, thus the intensity of loading fluctuation on rotor blades is weakened significantly, which is beneficial to improve rotor blade forced response.